Laou Kai Fook : a living intangible industrial/business heritage, case study of a traditional fabric and tailor shop in Shanghai - Sun, Yijun (The University of Hong Kong (Pokfulam, Hong Kong), 2015)
Traditional fabric and tailoring shops, which had a close relationship to the textile industry once flourished in Shanghai, used to play a vital role in people’s daily life and thus forming the culture of purchasing fabrics and tailoring. Nowadays, most of them are disappearing in a rapid speed without raising too many public concerns.